Nate & Margaret [videorecording (DVD)] - West, Natalie, 1956-; Ross, Tyler; McCahill, Conor; Hoffmann, Gaby, 1982- (Breaking Glass Pictures, 2012)
Nate & Margaret centers on a 19 year old film student named Nate, and his best friend Margaret, a 52 year old spinster who dreams of being a stand up comedian. Nate's audacious classmate Darla sets him up on a date with James, which causes Nate's new life to shake apart his friendship with Margaret, who must now go find a life of her own.